The Role of Human Capital Management in Enhancing the Competitiveness of Startup Companies - Fatmawaty , A. St. (CV. HEI PUBLISHING INDONESIA, 2025)
The rapid expansion of the startup ecosystem necessitates the strategic management of human talent as a core asset for sustained business viability and competitive differentiation. Accordingly, this study investigates the role of Human Capital Management (HCM) practices in enhancing startup competitiveness within dynamic and resource-constrained markets. A quantitative approach was employed by integrating official secondary data across three levels—firm, talent market, and ecosystem context—with primary HCM data collected from Jakarta-based startups as Indonesia’s national digital economy hub. Multiple regression analysis was used to examine the effects of key HCM variables, including training investment, equity-based compensation, and employee turnover, on performance indicators such as revenue growth and funding success. The findings reveal that higher investment in employee development and the provision of equity compensation have a positive and statistically significant impact on funding success and employee productivity. In contrast, elevated turnover rates exhibit a significant negative relationship with revenue growth, highlighting the critical importance of employee retention. Overall, the study concludes that strategic and adaptive HCM practices oriented toward long-term value creation are essential for startups operating in highly competitive ecosystems.